2018
DOI: 10.1111/ivb.12220
|View full text |Cite
|
Sign up to set email alerts
|

Species richness and similarity of metazoan parasite communities in three species of leatherjacket (Oligoplites: Pisces: Carangidae) from the Pacific coast of Mexico

Abstract: Species richness and similarity in metazoan parasite communities of fishes can be influenced by several biotic (age, body size, vagility, feeding and social behavior, among others), and local abiotic (temperature, salinity, etc.) factors. The parasite communities of three species of Oligoplites, marine fishes from the Pacific coast of Mexico, were quantified and analyzed. Four hundred sixty‐eight leatherjackets (O. altus, n=94; O. saurus, n=260; and O. refulgens, n=114) were collected from February 2016 to Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Aggregation is a typical parasite dispersion pattern in marine fishes (Alves & Luque, ; Amarante, Tassinari, Luque, & Pereira, ; Iannacone et al, ; Rohde, ; Santos‐Bustos et al, ; Villalba‐Vasquez et al, ). Dispersion index ( DI ) values of the parasite communities indicated that 70% of the identified parasite species exhibited an aggregate dispersion in one or more sampling years (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Aggregation is a typical parasite dispersion pattern in marine fishes (Alves & Luque, ; Amarante, Tassinari, Luque, & Pereira, ; Iannacone et al, ; Rohde, ; Santos‐Bustos et al, ; Villalba‐Vasquez et al, ). Dispersion index ( DI ) values of the parasite communities indicated that 70% of the identified parasite species exhibited an aggregate dispersion in one or more sampling years (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Diet diversity and host body size were also determinants of higher species richness and diversity in the E. lineatus parasite infracommunities (Figure ). Host diet is vital in structuring the intestinal parasite communities of marine fish (Luque et al, ; Santos‐Bustos et al, ; Sasal et al, ; Tavares & Luque, ; Villalba‐Vasquez et al, ). As mentioned above, the predatory habits and voracity characteristic of E. lineatus (Collette & Nauen, ) expose individuals of this species to a wide variety of parasites (e.g., digeneans, cestodes, acanthocephalans, and nematodes) acquired through ingestion of infected prey.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations